The quantity theory of money: An assessment of its real linchpin prediction - Claude Hillinger; Bernd Süssmuth (Center for Economic Studies and ifo Institute (CESifo), 2010)
This study approaches the Quantity Theory of Money at a conceptual level, asking how it can be most reasonably interpreted and quantitatively assessed. The resulting approach is straightforward. Unlike studies relying on other methods we find evidence of its linchpin prediction that is not limited to periods of high inflation.
Keywords: B22; E31; E41; E52; 330; quantity theory of money; Quantitätstheorie; Inflation; Prognoseverfahren